2022
DOI: 10.3390/atmos13122088
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Organic Micropollutants in Fine Particulate Matter in Hanoi Metropolitan Area, Vietnam

Abstract: Rapid urbanization has led to increased environmental pollution in Vietnam, especially air pollution issues. In this study, we used gas chromatography-mass spectrometry with an automated identification and quantification system database to detect and quantitate compounds in atmospheric fine particulate matter (PM2.5). A total of 288 compounds classified in 19 pollutant categories based on their origins were detected in PM2.5 samples collected in three areas of Hanoi during winter. The total content of substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…For example, in wastewater matrices analyzed by GC/MS in Japan, Ryo Omagari was able to detect the presence of 474 compounds in the influent wastewater soluble fraction [19]. In dust samples collected in Vietnam, Le Quang Huong et al identified 288 compounds [16], and Trinh Thu Ha et al identified 277 compounds in flood water samples [36]. Almost 200 compounds can be detected in sediment samples [10,12,38].…”
Section: Aiqs-db Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in wastewater matrices analyzed by GC/MS in Japan, Ryo Omagari was able to detect the presence of 474 compounds in the influent wastewater soluble fraction [19]. In dust samples collected in Vietnam, Le Quang Huong et al identified 288 compounds [16], and Trinh Thu Ha et al identified 277 compounds in flood water samples [36]. Almost 200 compounds can be detected in sediment samples [10,12,38].…”
Section: Aiqs-db Applicationmentioning
confidence: 99%
“…Since its inception, AIQS-DB has been widely utilized in numerous studies to concurrently analyze organic compounds in various sample matrices, such as river water samples [3][4][5][6], groundwater samples [7][8][9], sediment samples [10][11][12], wastewater samples [13][14][15], and dust samples [16][17][18]. Moreover, AIQS-DB has been adapted for use with other analytical instruments, including LC/MS/MS and LC-TOF/MS, making it an expedient, comprehensive, cost-effective, and scalable approach for identifying organic micro-pollutants [6].…”
Section: Introductionmentioning
confidence: 99%